ENHANCING STUDENTS VOCABULARY MASTERY THROUGH DRILLING TECHNIQUE AT JUNIOR HIGHT SCHOOL - Agustin, Pirda; Elisa, Henry; Tuti, Tuti (English Language Education Study Program, 2024)
The aims of this research are to describe the students participation improvement and vocabulary mastery in learning activities through the implementation of drilling technique. This research was carried out due to the students having low motivation in learning. Besides, they got trouble mastering and memorizing the vocabulary so that they had the poor vocabulary. The researchers applied Classroom Action Research; the data of this research was analysed in both qualitative and quantitative methods. The researchers used observation, measurement, interviews and documentation technique to collect the data. The instruments are observation checklist, field notes, tests and interview guidelines. The findings showed that there is an improvement students vocabulary mastery and participation in learning activities. In cycle I, the average score of students' vocabulary mastery was 48% and in cycle II it was 77%. The students participation in learning activities was also improved, in cycle I was 68% while in cycle II was 79%. It can be inferred that drilling technique can improve the students students participation and vocabulary mastery in learning activities at seventh-grade in SMPN 03 Sokan.